OP0154-HPR EFFECT OF NURSE-LED-CARE ON PATIENT OUTCOMES IN RHEUMATOID ARTHRITIS IN GERMANY: A MULTICENTRE RANDOMISED CONTROLLED TRIAL. (2nd June 2020) - Hoeper, J. R.; Gauler, G.; Meyer-Olson, D.; Rockwitz, K.; Steffens-Korbanka, P.; Stille, C.; Walter, J.; Welcker, M.; Wendler, J.; Zeidler, J.; Hoeper, K.
Abstract : Background: Inflammatory rheumatic disorders are very complex and require high medical resources. However, there is a shortage of care for these patients, which results in suboptimal reach of therapy objectives. Nevertheless, these very objectives need to be pursued quickly to prevent permanent joint damage. In order to ensure adequate care, multidisciplinary teams which include clinical nurse specialists are required. These clinical nurse specialists play an important role in improving standard-of-care in addition to the rheumatologist. The current standard of care ensures that essential medical provision remains intact, however, psychological, social, rehabilitative and educational needs are often skipped due to time constraints. While studies from e.g. the UK and Denmark have already supported the non-inferiority of nurse-led care (NLC) 1, no such studies have yet been published in Germany. Objectives: To demonstrate the non-inferiority of NLC to the current standard-of-care, rheumatologist-led care (RLC), for patients with seropositive rheumatoid arthritis (RA) with induction, escalation or change of therapy regarding disease activity as well as different patient reported outcomes (PROs). Methods: This trial was conducted as a prospective multi-centered RCT with a non-inferiority design over the course of 12 months. Based on power calculations, 236 adults with RA were included in the study and randomized to either NLC or RLC. The primary outcome measure is disease activity (DAS28), assessed at baseline (T0), 6 weeks (T1), 3, 6, 9, and 12 months (T3, T6, T9, T12). Secondary measures are health related quality of life (RAID), functionality (FFbH) and depression (PHQ9). Results: There are no significant differences between intervention group (IG) (n=117) and control group (CG) (n=119) at baseline. The mean age of the IG is 58.80 years (SD=12.09) and of the CG 58.34 years (SD=11.72). 72.4% of the IG and 78.1% of the CG are female. The mean duration of symptoms was 147 months (SD=144.63) for the IG and 116 months (108.89) for the CG. The mean DAS28 for the IG is 4.36 (SD=1.24) and 4.51 (SD=1.24) for the CG. A mixed one-way repeated measures ANOVA showed that the DAS28 improves significantly over time, Huyn-Feldt F (4.42, 751.72) = 105.701, p < .001, partial η 2 = 0.383, but the interaction of the DAS28 and the randomization is not significant, Huyn-Feldt F (4.42, 751.72) = 1.464, p = 0.260, partial η 2 = 0.009. No main effect for randomization was found, meaning that the IG and CG did not differ significantly, F (1, 170) = 1.005, p = 0.317, partial η 2 = 0.006. The Mann-Whitney-Test showed that the change of the secondary outcomes does not depend on the randomization FFbH U = 4978.50, Z = -.755, p =.450. RAID U = 5121.00, Z = -.539, p =.590. PHQ9 U = 4800.50, Z = -1.281, p =.200. The secondary outcomes improve significantly over time, as shown by a Wilcoxon Signed Rank test for the FFbH Z = -5.589, p < .001, the RAId Z = -9.884, p < .001 and the PHQ9 Z = -7.960, p < .001. Conclusion: The results support the non-inferiority of NLC in the management of RA regarding the primary and secondary outcome measures and provide first evidence that NLC could improve care and help carry the doctors' workflow. References: [1]de Thurah A, Esbensen BA, Roelsgaard IK, et al. Efficacy of embedded nurse-led versus conventional physician-led follow-up in rheumatoid arthritis: a systematic review and meta-analysis. RMD Open 2017;3:e000481. Disclosure of Interests: Juliana R Hoeper: None declared, Georg Gauler Consultant of: Abbvie, Lilly, MSD, Speakers bureau: Abbvie, Celgene, Novartis, Sanofi, , Dirk Meyer-Olson Grant/research support from: Novartis, Sandoz Hexal, Consultant of: Abbvie, Amgen, Bristol Myers Squibb, Chugai, Lilly, Mylan, Novartis, Sandoz Hexal, Sanofi, Speakers bureau: Abbvie, Bristol Myers Squibb, Chugai, Lilly, Novartis, Pfizer, Sandoz Hexal, Sanofi, Karin Rockwitz Consultant of: Janssen Cilag, Speakers bureau: Janssen Cilag, Patricia Steffens-Korbanka Consultant of: Abbvie, Chugai, Novartis, Sanofi, Mylan, Lilly, Speakers bureau: Abbvie, Chugai, Novartis, Sanofi, Lilly, Carsten Stille: None declared, Jochen Walter Consultant of: Pfizer, Speakers bureau: AbbVie, Frauenhofer Institut, Gilead, Janssen-Cilag, Medac, Novartis, Pfizer, Martin Welcker Grant/research support from: Abbvie, Novartis, UCB, Hexal, BMS, Lilly, Roche, Celgene, Sanofi, Consultant of: Abbvie, Actelion, Aescu, Amgen, Celgene, Hexal, Janssen, Medac, Novartis, Pfizer, Sanofi, UCB, Speakers bureau: Abbvie, Aescu, Amgen, Biogen, Berlin Chemie, Celgene, GSK, Hexal, Mylan, Novartis, Pfizer, UCB, Joerg Wendler Consultant of: Janssen, AbbVie, Sanofi, Speakers bureau: Roche, Chugai, Janssen, AbbVie, Novartis, Jan Zeidler: None declared, Kirsten Hoeper Consultant of: AbbVie, Celgene, , Speakers bureau: Abbvie, Chugai, Novartis, Lilly, Celgene, Sandoz Hexal